IKN ACCOMPANIES THE PROPERTY INDUSTRY - Rosiana Prihandayani, Intan; Maya Kumala Sari, Herlinda; Prapanca, Detak (JURNAL EKBIS, 2025)
The property sector plays an important role in a country's economy and is an indicator of economic growth. The development of the Indonesian Capital City (IKN) in East Kalimantan is estimated to have a significant impact on the stock prices of the property companies involved. This study aims to analyze the effect of profitability, liquidity, and leverage on the stock prices of the property sector before and after the announcement of the IKN project. The research method used is an event study with a quantitative approach, using data from property companies listed on the Indonesia Stock Exchange (IDX). The results of the analysis show that liquidity and leverage have a significant effect on stock prices, while profitability does not have a significant effect. In addition, there was a change in investor investment strategies after the announcement of the IKN development, where leverage began to become a major consideration in assessing property sector stocks. This study provides insight for investors and stakeholders into the financial factors that influence stock prices in the context of large infrastructure projects.